Semiotic Analysis of "Euro 2020" Tournament’s Memes on Social Media Twitter - Irfan Fauzan; Tiarma Ika Yuliana; Rr. Astri Indriana Octavita (JEdu: Journal of English Education, 2021)
The objective of this research is to reveal the meaning of Euro 2020 Tournament memes in social media using a study of Roland Barthes's semiology. The method of the research is qualitative using technical analysis of Roland Barthes semiology. The technique used to collect data is based on two resources. The primary data are collections of memes about Euro 2020 on social media Twitter and the second are references supporting the topic of the research. The result of the study is to show that the meme creators tried to publish the social condition that happened during Euro 2020 Tournament through memes. The conditions were presented in some types of memes, such as troll memes, and comedy memes